THE EQUILIBRIUM BETWEEN ISLAMIC INVESTMENT PRIORITIES - Seraj Moh Ekhlat; Murni Yusoff; Shahir Akram Hassan (Journal of Islamic, Social, Economics and Development, 2024)
A sign of the overall excellence of the Islamic economic system is that it has a standard system which is eager to systematise investment and management procedures. One of the Islamic standard systems is investment priority. This article aims to examine the issue of establishing investment priorities and how to balance those priorities in light of current global conditions that may encourage investment organizations to overachieve in search of tangible profit. This was accomplished by responding to the questions posed in: What is the nature of investment in Islam? What are the Islamic investment priorities? How can the investment priorities be balanced? Are Islamic investment priorities complementary or contradictory? This study is a qualitative by using document research as instrument and analyzed using content analysis. According to the categories of human needs defined in Islamic financial doctrine (Necessities- Daruriyat, Needs- Hajiyyat, and Luxures- Tahsiniyyat), this stemmed from and was predicated on Sharia's purposes (Maqasid Al Shariah). The research also found that adhering to such criteria achieves Shariah goals (Maqasid Al Shariah) as well as economic efficiency. Islam has established balance for Sharia goals based on their mutual interests (Maslahah) on the one hand, and their abuses (Mafased) on the other hand. The Islamic investment model operates to balance diverse demands in accordance with jurisprudential criteria.